Do Auditors Objectively Evaluate Their Subordinates' Work? - Tan, Hun-Tong; Jamal, Karim (The Accounting Review, 2001)
In this study, we investigate whether audit managers' assessment of the quality of work their subordinates perform is influenced by the managers' prior impressions of these subordinates, and whether managers whom the firm considers outstanding are less susceptible to such an effect. We conduct an experiment using actual audit senior-manager teams. Each senior and manager participating in the experiment has been classified by his or her firm as either outstanding or average. Each manager is paired with two audit seniors (one outstanding senior and one average senior), and each evaluates the memos written by his or her paired seniors. Managers evaluate the quality of the memos twice: (1) first, with the identities of the seniors indicated on the memos, and (2) later, when the seniors' identities are not explicitly revealed. Results show that average managers evaluate memos written by outstanding seniors more favorably than those written by average seniors when they know the identities of the memos' authors, but not when the identities of the seniors are not revealed. Outstanding managers do not appear susceptible to this effect.